THE OVERVIEW OF PARENTING IN CHILDREN IN URBAN AREAS - Naya Erna Wati (STIKes Kepanjen, 2023)
Background: The family is the first place where children are raised, and in special waysadopted by the family in raising their children is called parenting. Families have differences culture and its role in the formation of children's character.Parenting patterns can be influenced by many factors, including: culture, social, education, economy, age of parents, and work etc. Objective: This study aims to determine the description of parenting in urban communities and the tendency of violent behavior in children. Methods: The research design is correlational with a cross-sectional approach. The population were parents (mother) who had children. The sampling technique used total sampling with a sample size of 50 respondents. Results: The distribution of parenting styles for children in urban areas is mostly in the moderate category, and the frequency distribution of violent behavior tendencies in the majority of children is mostly in the medium category. Conclusion: It is hoped that the government can collaborate with health services to provide services or counseling and that can provide socialization that emphasizes aspects of increasing parents' understanding of parenting to promote care, safety, closeness without violence and create an environment without conflict with children.